The Storytelling Initiative: Community Podcasting at the Frontlines of Climate and Environmental Crises - Langdon, Jonathan; Harvey, Blane; Cameron, Sheena (The Canadian Journal of Action Research, 2025)
Stories move people, and storytelling constitutes an important form of local action in the face of the multiple crises we confront at this time. Community-led podcasting is a powerful medium for conveying these stories, disrupting mass media’s dominant narrative to reframe discourse and amplify local perspectives on social and ecological issues. The Storytelling Initiative worked with frontline communities and organizations confronting climate and environmental crises to not just be subjects of podcasts, but authors and producers of their own stories. Each podcast shares a unique story of collective learning and action, ranging from youth in informal settlements building leadership to contend with climate impacts in their communities, to the use of legal mechanisms by communities in Pakistan to halt destructive government-sponsored development projects, to voices from the Arctic bringing gender relations into discussions of climate in the region. This article shares the community participatory podcasting approach used to work with the seven podcasting teams that produced these stories, and the community of practice that emerged as a result. It unpacks ways in which the stories they share push for wider change from the standpoint of their respective struggles, and invites listeners to learn with them. It also reflects on the potential of participatory podcast production and analysis as an emergent method of participatory action research.